THE SWALLOW’S NEST TAX COLLECTION IN INCREASING LOCAL OWN-SOURCE REVENUE BASED ON THE LOCAL REGULATION OF SELUMA REGENCY NUMBER 5 OF 2011 ON LOCAL TAXES - Thaariq Alfathan; Amirizal Amirizal; Amancik Amancik (Universitas Bengkulu, 2023)
The implementation of the swallow’s nest tax collection in Seluma Regency is carried out based on the Local Regulation of Seluma Regency Number 5 of 2011 on Local Taxes. The distribution of tax is carried out by using a self-assessment system which this system gives confidence to the taxpayers to determine the amount of tax payable that must be borne. However, this system can work successfully if the taxpayers have awareness and compliance in paying their taxes. The swallow’s nest tax can contribute to the Local Own-Source Revenue of Seluma Regency, however, there are still some obstacles in collecting it, especially for taxpayers who are considered to have bad faith. This research aims to analyze (1) the implementation of the swallow’s nest tax collection in increasing the Local Own-Source Revenue is based on the Local Regulation of Seluma Regency Number 5 of 2011 on Local Taxes; (2) obstacles and solutions to the swallow’s nest tax collection in increasing the Local Regulation of Seluma Regency Number 5 of 2011 on Local Taxes. The type of this research was descriptive. The type of research in this legal research was empirical legal research. The results of this research showed that (1) the collection of the swallow’s nest tax in increasing Local Own-Source Revenue based on the Local Regulation of Seluma Regency Number 5 of 2011 on Local Taxes had not been maximal because the swallow’s nest tax revenue was still very low and the system used in tax collection was a self-assessment system in Seluma Regency. Moreover, (2) the obstacle of the swallow’s nest tax collection in increasing the Local Regulation of Seluma Regency Number 5 of 2011 on Local Taxes was caused by the lack of awareness of taxpayers in reporting, registering, calculating, and paying swallow’s nest taxes. To overcome the obstacle, the Local Development Planning Agency was in collaboration with the Seluma District Attorney (Kejari), the Resort Police Force (Polres) of Seluma Regency, and the Seluma One-Stop Integrated Investment and Licensing Service Office (DPMPPTSP). Keywords: Swallow’s Nest Tax, Local Own-Source Revenue, the Local Government Regulation of Seluma Regency.